Pengaruh Sistem Reward Dan Sistem Punishment Terhadap Kepatuhan Karyawan Pada Pt Bank Muamalat KCU Mamuju - Azzahra, Sari Zalni Juni; Martini, Andi Indra; Halim, Agus (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Bank Muamalat Indonesia Tbk. Mamuju Branch is one of the banking companies located in Mamuju Regency, West Sulawesi, on Jalan Urip Sumoharjo, Karema, Mamuju District, Mamuju Regency, which has grown rapidly to date. Since its establishment in 2009 in Mamuju, it has been led by Mr. Ansar. This is because the division of South Sulawesi into West Sulawesi has increased the demand for Islamic banking in the Mamuju area. In addition, the majority of the population or community in Mamuju Regency is Muslim. This study was conducted with the aim of determining the effect of the reward and punishment systems on employee compliance at PT Bank Muamalat KCU Mamuju. The respondents in this study were all employees at PT Bank Muamalat Indonesia KCU Mamuju, with a population of 33. The sample size was determined using total sampling technique with 33 respondents. The formulas used in this study were multiple linear regression, validity test, reliability test, t-test, F-test, and coefficient of determination test. The results showed that the reward system had a significant partial effect on employee compliance. The punishment system also had a significant partial effect on employee compliance. Simultaneously, the Reward System and Punishment System have a significant effect on Service User Satisfaction, with a contribution of 49.2%. These findings indicate that although the Reward System and Punishment System have been proven to contribute to employee compliance, there are still other factors that also play an important role but have not been revealed in this study